Solving Knapsack Problem using Dynamic Programming - Violina, Sriyani; Herlistiono, Iwa Ovyawan (CENTRAL ASIA AND THE CAUCASUS, 2022)
Dynamic Programming is an algorithm or method in solving complex problems by describing how to solve them in several stages by dividing the problem into simpler problems. So that each stage of completion is related to each other until a final solution is produced. The Knapsack problem is a combinatorial problem, which is given a set of items, each of which has a weight and value. Knapsack solution using Dynamic Programming does not always get optimal results.